2019
DOI: 10.1128/mbio.01538-19
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus Infection of Placental Trophoblasts Triggers Endoplasmic Reticulum Stress-Mediated Cell Death and Fetal Loss via Type IV Secretion System-Dependent Activation of CHOP

Abstract: Subversion of endoplasmic reticulum (ER) function is a feature shared by multiple intracellular bacteria and viruses, and in many cases this disruption of cellular function activates pathways of the unfolded protein response (UPR). In the case of infection with Brucella abortus, the etiologic agent of brucellosis, the unfolded protein response in the infected placenta contributes to placentitis and abortion, leading to pathogen transmission. Here we show that B. abortus infection of pregnant mice led to death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 41 publications
4
47
1
Order By: Relevance
“…Our study supports previous findings that suggest that the trophoblast may respond differently to different bacteria [46][47][48][49][50][51][52][53]. The results support the existence of separate mechanisms of bacterial recognition by trophoblasts, or the presence of bacterial products leading to alternative inflammatory/anti-inflammatory responses.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our study supports previous findings that suggest that the trophoblast may respond differently to different bacteria [46][47][48][49][50][51][52][53]. The results support the existence of separate mechanisms of bacterial recognition by trophoblasts, or the presence of bacterial products leading to alternative inflammatory/anti-inflammatory responses.…”
Section: Resultssupporting
confidence: 91%
“…The degree to which trophoblasts participate in the control of potential placental-colonizing microbiota requires further study. Furthermore, previous studies have suggested that trophoblasts may respond differently to different bacteria [46][47][48][49][50][51][52][53]. In this paper, we compare the cytokine patterns exhibited by Swan 71 (Sw.71), immortalized human first trimester trophoblast cells [54], after in vitro interactions with E. coli (a common urogenital pathogen), L. jensenii (a vaginal commensal), and L. crispatus (a hypothesized mutualist and sentinel of the human vaginal ecosystem) [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…However, ER stress caused by microbial infection is usually long term. ER stress has been proven to be associated with inflammatory diseases caused by infections of various microorganisms, such as acute viral myocarditis, chronic hepatitis C virus, tuberculosis, and placental inflammation (Cai et al 2015;Dash et al 2019;Lim et al 2015;Byndloss et al 2019). In order to verify whether Tp0768 induces macrophages to produce ER stress, we observed the ultrastructure of ER using transmission electron microscopy Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Once Brucella has impaired phagosome-lysosomal fusion, it replicates in the ER compartment, its replicative niche. Following replication, BCVs interact with host autophagic proteins Beclin1, ULK1, Atg14, and the IRE1α-UPR signaling axis for bacterial egress and the start of replication cycles within newly infected cells [ 64 , 65 , 66 , 67 ].…”
Section: Niche and Reservoirmentioning
confidence: 99%